Development of E-module Basic Physics Practicum Guide to Train Students' Science Process Skills - Arka Yanitama; Prasetyo Listiaji (Universitas Negeri Semarang, 2023)
The practicum guide is an important reference in practical lectures. As a result of the Covid-19 pandemic which has lasted more than two years, some media can be converted into digital media. The basic physics practicum guide e-module was developed during the pandemic with the aim of being able to be used by students who carry out independent practicums at their respective homes using virtual laboratories. In its development, the created e-module is also intended to train students' science process skills. The development was carried out using the ADDIE model and showed that the results of expert validation were very valid. At the implementation stage, it was then tested using a test with questions containing indicators of science process skills showing 77.27% in the medium category, 13.64% low, and 9.09% high. The results of the implementation show that most of the indicators that have good scores are the basic skills of observing, measuring, and predicting.